Timonius pannosus - Tsen, S.; Colin Ruzelion Maycock; Khoo, E.; Nilus, R.; Sugau, J.; Tanggaraju, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Timonius pannosus is only known from Melangkap Tomis village, Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 4 km2. This species is found outside protected areas. There is a continuing decline in habitat quality caused by its locality near human settlements. Hence, it is assessed as Critically Endangered. Timonius pannosus is endemic to Sabah, Malaysia. It is confined to the west side of Kinabalu Park.